Penerbitan Kartu Keluarga Bagi Pasangan Perkawinan Tidak Tercatat Perspektif Maslahah Mursalah - Murti, Anis; Hafiz, Abdul; Sitorus, Iwan Ramadhan (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: Data collection techniques using the Document Method (Documentation). The conclusion results state that, 1) As for the juridical review of Issuance of family cards for unregistered married couples, this is the right policy. However, the issuance of a family card for unregistered married couples does not constitute state legitimacy in legalizing unregistered marriages, but only as an affirmative policy for the time being until marriage registration or marriage registration/certification of marriages is carried out. Family cards for unregistered spouses are a solution to population administration problems. However, the Family Card does not legalize the occurrence of a marriage, but only accelerates the population administration data collection process at the Population and Civil Registry Service. 2) Issuance of family cards for married couples who are not registered according to the perspective of maslahah mursalah is included in Al-Maslahah al-Tahsiniyah, is a maslahah whose human life needs do not reach the dharuri level, nor do they reach the hajji level, but these needs need to be met in order provide perfection and beauty to human life. Maslahah in the form of tahsini is also related to the five basic human needs. Benefit in this case is guaranteeing population administration rights for unregistered married couples, realizing the wishes of unregistered married couples in obtaining population rights, realizing orderly national population administration, collecting data on unregistered marriages to be encouraged to perform marriage certificates, and realizing population administration which is not discriminatory.Keywords: Family Card, Unrecorded Marriage, Maslahah Mursalah Perspective Abstract: Teknik pengumpulan data menggunakan Metode Dokumen (Documentation). Hasil kesimpulan menyatakan bahwa, 1) Adapun tinjaun yuridis terhadap Penerbitan kartu keluarga bagi pasangan perkawinan tidak tercatat adalah kebijakan yang sudah tepat. Akan tetapi, penerbitan kartu keluarga bagi pasangan nikah tidak tercatat bukan merupakan legitimasi negara dalam melegalkan perkawinan tidak tercatat, namun hanya sebagai kebijakan afirmatif untuk sementara waktu sampai dilaksanakan pencatatan perkawinan atau isbat nikah/pengesahan perkawinan. Kartu Keluarga bagi pasangan tidak tercatat merupakan solusi terhadap masalah administrasi kependudukan. Akan tetapi, Kartu Keluarga tersebut tidak mengesahkan terjadinya suatu perkawinan, melainkan hanya mempercepat proses pendataan administrasi kependudukan pada Dinas Kependudukan dan Catatan Sipil. 2) Penerbitan kartu keluarga bagi   pasangan perkawinan tidak tercatat menurut persepktif maslahah mursalah masuk ke dalam Al-Maslahah al-Tahsiniyah, adalah maslahah yang kebutuhan hidup manusia kepadanya tidak sampai pada tingkat dharuri, juga tidak sampai tingkat hajji, namun kebutuhan tersebut perlu dipenuhi dalam rangka memberi kesempurnaan dan keindahan bagi hidup manusia. Maslahah dalam bentuk tahsini tersebut juga berkaitan dengan lima kebutuhan pokok manusia. Kemaslahatan dalam hal ini yakni menjamin hak administrasi kependudukan bagi pasangan perkawinan tidak tercatat, mewujudkan keinginan pasangan perkawinan tidak tercatat dalam mendapatkan hak-hak kependudukan, mewujudkan tertib administrasi kependudukan secara nasional, terkumpulnya data perkawinan tidak tercatat untuk didorong melakukan isbat nikah, serta terwujudnya administrasi kependudukan yang tidak diskriminatif.Kata kunci : Kartu Keluarga, Perkawinan Tidak Tercatat, Perspektif Maslahah Mursalah